2020
DOI: 10.1116/6.0000580
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing nanostructured nickel-rich lithium-ion battery cathodes via surface stabilization

Abstract: Layered, nickel-rich lithium transition metal oxides have emerged as leading candidates for lithium-ion battery (LIB) cathode materials. High-performance applications for nickel-rich cathodes, such as electric vehicles and grid-level energy storage, demand electrodes that deliver high power without compromising cell lifetimes or impedance. Nanoparticle-based nickel-rich cathodes seemingly present a solution to this challenge due to shorter lithium-ion diffusion lengths compared to incumbent micrometer-scale ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 38 publications
4
13
0
Order By: Relevance
“…Following synthesis, the NMC particles were uniformly coated with graphene and ethyl cellulose (GrEC) using a previously established solution-phase method. 25,27 The coating conformality was confirmed using SEM and transmission electron microscopy (TEM) (Figure 1a−c), which revealed the presence of a percolating network of graphene flakes throughout the electrode, consistent with prior work. 25,27,28 After fabricating electrodes with the GrEC powder (NMC-GrEC), the electrode was heated to pyrolyze the ethyl cellulose (EC) polymer, which largely volatilizes the EC, compacts the electrode, and generates a carbon residue that helps form a percolating, electrically conductive network among the graphene-coated NMC particles.…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…Following synthesis, the NMC particles were uniformly coated with graphene and ethyl cellulose (GrEC) using a previously established solution-phase method. 25,27 The coating conformality was confirmed using SEM and transmission electron microscopy (TEM) (Figure 1a−c), which revealed the presence of a percolating network of graphene flakes throughout the electrode, consistent with prior work. 25,27,28 After fabricating electrodes with the GrEC powder (NMC-GrEC), the electrode was heated to pyrolyze the ethyl cellulose (EC) polymer, which largely volatilizes the EC, compacts the electrode, and generates a carbon residue that helps form a percolating, electrically conductive network among the graphene-coated NMC particles.…”
Section: Resultssupporting
confidence: 81%
“…25,27 The coating conformality was confirmed using SEM and transmission electron microscopy (TEM) (Figure 1a−c), which revealed the presence of a percolating network of graphene flakes throughout the electrode, consistent with prior work. 25,27,28 After fabricating electrodes with the GrEC powder (NMC-GrEC), the electrode was heated to pyrolyze the ethyl cellulose (EC) polymer, which largely volatilizes the EC, compacts the electrode, and generates a carbon residue that helps form a percolating, electrically conductive network among the graphene-coated NMC particles. 24,25,27−30 Subsequent Raman spectroscopy of the electrode confirmed that the ratio of the D and G peaks decreased (at 1350 and 1580 cm −1 , respectively) (Figure S3), suggesting that EC decomposition resulted in a more graphitic carbon network that facilitates efficient charge transfer.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations